Rebamipide, a mucoprotective drug, inhibits NSAIDs-induced gastric mucosal injury: possible involvement of the downregulation of 15-hydroxyprostaglandin dehydrogenase - Tanigawa, Tetsuya (the Society for Free Radical Research Japan, 2011)
Prostaglandin E(2) plays an important role in the maintenance of gastric mucosal integrity. The level of biologically active prostaglandin E(2) in the tissue is regulated by the balanced expression of its synthetic enzymes, such as cyclooxygenase, and its catabolic enzyme, 15-hydroxyprostaglandin dehydrogenase. We examined the effect of rebamipide, a mucoprotective drug, on prostaglandin E(2) production and metabolism in the gastric tissue and its effect on indomethacin-induced gastric mucosal injury in mice. Rebamipide suppressed indomethacin-induced gastric mucosal injury. Suppressive effect of rebamipide on indomethacin-induced gastric mucosal injury was also observed in cyclooxygenase-2-knockout mice. The mice that were treated with rebamipide showed a 2-fold increase in cyclooxygenase-2 mRNA expression in the gastric tissue, whereas 15-hydroxyprostaglandin dehydrogenase mRNA expression markedly decreased as compared to vehicle-treated control mice. Rebamipide did not affect the expression of cyclooxygenase-1 in the gastric tissue. Rebamipide did not increase prostaglandin E(2) production in the gastric tissue; however, it induced a 1.4-fold increase in the concentration of prostaglandin E(2) in the gastric tissue as compared to vehicle-treated control mice. These results suggest that the suppressive effect of rebamipide on non-steroidal anti-inflammatory drugs-induced gastric mucosal injury can be attributed to reduced 15-hydroxyprostaglandin dehydrogenase expression, which increases the prostaglandin E(2) concentration in the gastric tissue.